Betaproteobacteria Limnohabitans strains increase fecundity in the crustacean Daphnia magna: symbiotic relationship between major bacterioplankton and zooplankton in freshwater ecosystem. (21st July 2015) - Peerakietkhajorn, Saranya; Kato, Yasuhiko; Kasalický, Vojtěch; Matsuura, Tomoaki; Watanabe, Hajime
Summary: How symbioses between bacteria and aquatic animals influence food webs in freshwater ecosystems is a fundamental question in ecology. We investigated symbiosis between a crustacean zooplankton D aphnia magna and its dominant bacterial symbiont L imnohabitans, an abundant and globally distributed freshwater B etaproteobacteria . Aposymbiotic juvenile D aphnia were prepared and exposed to any of four L imnohabitans sp. – L imnohabitans strains DM1, 2KL‐3, 2KL‐7 and L imnohabitans planktonicus strain II‐D5, all previously found in D . magna digestive tract or culture. Re‐infected D aphnia were cultured until they produced the first clutch of juveniles. L imnohabitans strain DM1 and L . planktonicus strain II‐D5 successfully re‐infected D aphnia through single exposure at the first instar juvenile stage. In contrast to aposymbiotic D aphnia that produced non‐viable juveniles, re‐infected D aphnia produced viable juveniles and increased fecundity to levels of that of symbiotic D aphnia . Re‐infected D aphnia did not increase their number of eggs nor growth rates. L imnohabitans strains 2KL‐7 and 2KL‐3 could not recover fecundity even in multiple exposures during culture. This study shows the functional evidence demonstrating that a single bacterium L imnohabitans regulates fecundity of the consumer D aphnia through symbiosis. Our results indicated that symbiotic relationship between major bacterioplankton and zooplankton is important for maintaining the population of zooplankton in freshwater ecosystems.